Plant protection measures to promote organic farming in Nepal: prospects and challenges - Pandey, Sunita; Aryal, Sunil; Aryal, Lok Nath; Timsina, Krishna Prasad (Journal of Agriculture and Natural Resources, 2022)
Organic farming is a production system that relies on ecosystem management rather than external agricultural inputs to sustain the health of soils, ecosystem and organisms. This needs enough organic plant protection measures and biological fertilizers by eliminating synthetic pesticides and fertilizers. An attempt was made to review current plant protection measures for organic farming in Nepal. Though some insect pests and diseases are very hard to control without the use of chemical pesticides, this is high time to produce agriculture products organically. There is ample prospect of organic production in Nepal utilizing traditional knowledge of Nepalese farmers and existing agri-biodiversity. The paper is focused on best utilization of local natural resources, indigenous knowledge and bio-control agents for plant protection in organic agriculture. The information related to organic plant protection measures are collected from various sources and are grouped. The authors have listed technologies on organic plant protection measures in Nepal and made some suggestions to improve the organic farming of the country.